Sistem Informasi Manajemen Aset Pada SMK Negeri 5 Bungo - S, M. Gasim; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2023)
Sekolah Menengah Kejuruan Negeri 5 Bungo is a form of formal education unit that organizes vocational education at the secondary education level. Asset management at SMK Negeri 5 Bungo is still done conventionally, where asset data is recorded and managed using Microsoft Office, this has an impact on asset management and asset reporting is not optimal. The aim of this research is to analyze the asset management information system at SMK Negeri 5 Bungo. This research method uses observation and interview techniques. The system design tool uses the Unified Modeling Language (UML) and prototype modeling. The result is an asset management information system at SMK Negeri 5 Bungo, the process of asset procurement, asset receipt, asset placement, asset write-off and reports